Plant protein hydrolysates: preparation of defined peptide fractions promoting growth and production in animal cells cultures - Franek, F; Hohenwarter, O; Katinger, H (Biotechnology progress, 2000)
A new approach was applied with the aim at producing plant protein hydrolysates less heterogeneous and less contaminated with nonpeptide substances than are the presently available digests. A significant reduction of nonprotein contaminants was achieved by extraction of the plant material, soy flour or wheat flour, with acetone prior to isolation of the protein. Enzymes of nonanimal origin, papain or Pronase, were used for protein hydrolysis. The components of the hydrolysates were resolved by low-pressure liquid chromatography. Separation of peptide fractions and of remaining nonpeptide contaminants was achieved using small-pore size-exclusion chromatography matrices, Sephadex G-15 or Biogel P-2. Individual peptide fractions, both from soy protein and from wheat gluten, varied substantially in their growth-promoting and production-enhancing activities when tested on a mouse hybridoma culture in protein-free medium. The highest enhancement of viable cell density in batch cultures was 180% of control, and the highest enhancement of final immunoglobulin concentration was more than 230% of control. The existence of marked differences in activity of individual peptide fractions leads to a suggestion that the hydrolysates may provide peptides exerting specific positive effects on cultured animal cells.
Keywords: rostlinné proteiny; buněčné dělení; peptidové fragmenty; Animals; Cell Line; Plant Proteins; zvířata; buněčné linie; Mice; Peptide Fragments; Cell Division; Chromatography, Liquid; hydrolýza; Hydrolysis; chromatografie kapalinová; myši